HUBUNGAN ANTARA PERSONAL HYGIENE DAN SANITASI TEMPAT DAGANG DENGAN ANGKA KUMAN PADA SATE AYAM DI KOTA PONTIANAK TAHUN 2015 - Supyansyah, Supyansyah; Rochmawati, Rochmawati; Selviana, Selviana (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Food safety is an important thing in Sanitary Science. This is because our environment is always associated with the human food supply. Food problems are usually occurred due to the food exposure to dirty surroundings, causing foods contamination than can harm human health. This study aimed at discovering the correlation of personal hygiene, sanitation of food stall area and the number of germs in chicken satay in Pontianak. Using observational analytic and cross sectional design, this study employed 45 food stalls. The data collecting tools used were questionnaire, observation and interview. The data were statistically tested by using Chi-square test and alternative test of Fisher’s Exact. The Results of bivariate test indicated that there was correlation of personal hygiene (p value = 0.029), PR = 3,143 95% CI (0887-11,141) and the number of germs in chicken satay in Pontianak. The variables that didn’t correlate with the number of germs in chicken satay were food sanitation (p value = 0.345) and clean water source (p value = 0,751). From the findings, the satay sellers are encouraged to wash their hands with clean and running water before and after handling food, cut their nails and use clean water to wash and cook the food. Keywords :Personal Hygiene, Sanitation, The Number of Germs, Chicken Satay